The Importance of Nepotym and Corruption Management in Institutions and the Economy of the Country - Fetahu, Driton (European Journal of Multidisciplinary Studies, 2017)
: Social, political and institutional factors play a major role in the country’s economic development and economic growth in developing and developed countries. Corruption, which is a symptom of deep institutional weaknesses, is one of the factors responsible for reducing investment and spending (for education and health), increasing income inequality, decreasing foreign direct investment, and allocating resources. It tends to grow faster than the dynamics implemented to neutralize it. Systematically, it has caused many disturbing problems in all countries of the world. Based on a Transparency International report. Corruption is one of the greatest contemporary challenges of the world. It determines good governance, leads to inefficient resource allocation, disrupts the private and public sector, and often affects the poor. The people in the world carry the phenomena that society has so far encountered but has neglected. Nepotism usually means hiring close relatives, close friends, regardless of their merits and abilities. While corruption poses a permanent threat to both the economic system and the country’s legal system. The purpose of this paper is; To assess the factors that have influenced the appearance and development of nepotism and corruption. Then, analyze the influence of nepotism and corruption in the country’s economy. The impact of nepotism on employment and the advancement of relatives in the important sector of the country as well as the influence of corruption and nepotism in justice institutions. The research results will be useful for researchers who will be concerned with analyzing the influential factors of nepotism and corruption.